Simulation-Based Performance Evaluation of Hierarchical Routing Protocols for Wireless Sensor Networks - Elvis, Obi; Umar, Abubakar; Mikail, Shamsudeen A.; Ezekiel, Agbon E.; Maina, Saleh A. (Journal of Intelligent System and Telecommunication, 2025)
Wireless Sensor Networks (WSNs) find widespread use in monitoring and data collection for many applications but are faced with tremendous challenges such as limited energy resources, scalability, and latency. Efficient routing protocols are essential in alleviating these challenges, extending network lifetime, and optimizing energy consumption. Among the numerous solutions proposed, hierarchical routing protocols have emerged as effective strategies for improving energy efficiency, minimizing latency, and enhancing network scalability. Despite their potential, comprehensive comparative evaluations of multiple hierarchical routing protocols under diverse operational conditions remain limited in the literature. This paper addresses this gap by conducting an extensive simulation-based performance evaluation of four hierarchical clustering protocols—Low-Energy Adaptive Clustering Hierarchy (LEACH), Energy-Aware Multi-Hop Multi-Path Hierarchical (EAMMH), Power-Efficient Gathering in Sensor Information Systems (PEGASIS), and Hybrid Energy-Efficient Distributed (HEED)—for WSNs A MATLAB-based simulation approach was employed to analyze these protocols using key performance metrics: energy consumption, network lifetime, latency, throughput, and scalability. The results indicate that PEGASIS offers the best energy efficiency and has a longer network lifespan than the other algorithms and is thus suitable for large-scale, long-duration deployments. HEED has the lowest latency and is thus highly suitable for real-time applications, and EAMMH delivers the highest throughput, which is suitable for high data transmission. While LEACH is energy-consuming, it is still a viable option for small-scale networks due to its simplicity. However, it shows poor scalability and a shorter network lifetime compared to the other algorithms. This comparative study reveals essential trade-offs between energy efficiency, latency, scalability, and throughput of WSN clustering protocols and offers helpful insights for the selection of the most appropriate protocol based on some application requirements. The findings become part of the efforts to continue enhancing WSN performance and extend their applicability to diverse real-world applications.